A Companion to folklore - Bendix, Regina F.; Hasan-Rokem, Galit (Chichester, West Sussex, [England] Wiley-Blackwell, 2014)
"A Companion to Folklore presents an original and comprehensive collection of essays from international experts in the field of folklore studies. Unprecedented in depth and scope, this state-of-the-art collection uniquely displays the vitality of folklore research across the globe. An unprecedented collection of original, state of the art essays on folklore authored by international experts Examines the practices and theoretical approaches developed to understand the phenomena of folklore Considers folklore in the context of multi-disciplinary topics that include poetics, performance, religious practice, myth, ritual and symbol, oral textuality, history, law, politics and power as well as the social base of folklore"--Provided by publisher.
"Copyright 2012 by John Wiley & Sons, Ltd."--Title page verso.
Includes bibliographical references and index.
Keywords: Folklore -- Study and teaching; Folklore -- Cross-cultural studies